Mild and Stereoselective Synthesis of (1E,3E)-Dienes through Silver(I)-Catalyzed β-Hydride Migration from Allylic α-Diazo Esters - Sá, Marcus M.; Moro, Pedro A. M.; Russo, Theo V. C.; Port, Vinicius C.; Caramori, Giovanni F. (Synthesis, 2024)
A mild procedure for the diastereoselective preparation of functionalized 1,3-dienes and their synthetic versatility are described herein. The silver-catalyzed decomposition of α-diazo-γ,δ-unsaturated esters through β-hydride migration at room temperature resulted in the stereoselective formation of 12 conjugated (1E,3E)-dienes. Further synthetic post-modifications included intramolecular Heck reaction and hydrogenation, leading to a novel substituted indene and an aliphatic diester, respectively. To rationalize the observed reaction outcome, a computational investigation of the mechanisms was conducted, emphasizing the importance of factors such as metallocarbenoid stability, substituent effects, and microkinetics simulations to better understand the reaction intricacies.
Keywords: α-diazo carbonyl compounds; silver-catalyzed reaction; β-hydride migration; 1,3-dienes; stereoselective catalysis; computational methods